Structural Studies of Norditerpenoid Alkaloids: Conformation Analysis in Crystal and in Solution States. Issue 15 (6th April 2021) - Zeng, Ziyu; Kociok‐Köhn, Gabriele; Woodman, Timothy J.; Rowan, Michael G.; Blagbrough, Ian S.
Abstract: Conformational analyses are presented of several pharmacologically important norditerpenoid alkaloids (NDAs), in crystal and in solution states. Crystal data of 8 NDAs (4 free bases and 4 salts) were obtained, in which crassicauline A, aconitine HCl, and methyllycaconitine HClO4 are reported for the first time. 1D/2D NMR spectroscopies of 7 NDAs (5 free bases and 2 salts) were recorded comprehensively. Crystal conformations of NDAs are described with a revised cyclohexane ring nomenclature. The A/E‐rings of NDA‐free bases exist in twisted‐chair/twisted‐chair conformations, leading to examples of the 1 H NMR effect of steric compression shown in the A‐ring. The A/E‐rings of NDA salts adopt boat/chair crystal conformations, as does the protonated synthetic [3.3.1]azabicycle in its crystal lattice. However, in aqueous solutions at physiological pH, this protonated analogue adopts a true chair/true chair conformation where the NDA salts retain their twisted boat/twisted chair conformations. Abstract : The A/E‐[3.3.1]azabicyclic rings of norditerpenoid alkaloids adopt twisted‐chair/twisted‐chair conformations, causing the 1 H NMR spectroscopic effect of steric compression of 2‐Ha where the N ‐atom lone‐pair electrons of these norditerpenoid alkaloids partly overlap with 2‐Ha . This effect is shown to be more significant in synthetic [3.3.1]azabicycles where the analogues adopt true‐chair/true‐chair conformations.